Theoretical study on wireless power transfer system via magnetic resonant coupling - Zhang, Xu (2012)
Wireless power transfer via magnetic resonant coupling is a cutting-age technology which enables effective mid-range power transmission while the traditional inductive coupling WPT system failed to do so. Previous research papers successfully demonstrated the high efficiency of magnetic resonant coupling wireless power transfer technology, however the prior works that were more focused on static transmission distance condition were unable to fulfil more practical design requirements such as a moving user with laptop.